Proximate composition and antioxidant activity of dried belimbing dayak (Baccaurea angulata) fruits - Khir Jauhari, Nurhazni; Ibrahim, Darina; Ibrahim, Muhammad; Yahya, Mohammad Nor Adros; Md. Nor, Norazmir; Md. Isa, Khairil Anuar; Ayob, Mohd. Khan; Omar, Muhammad Nor; Hazali, Norazlanshah (Penerbit UKM, 2013)
Baccaurea angulata or locally known as ‘belimbing dayak’ or ‘belimbing hutan’ is an underutilized fruit indigenous to Borneo with its proximate analysis and antioxidant values are yet to be explored. Proximate analysis and antioxidative properties of oven-dried B. angulata fruits of three fractions; whole fruit, skins and berries were evaluated. From the analysis conducted, whole fruit, berries and skins fraction of B. angulata contained 2.83%, 5.15% and 0.28% of total fat; 3.11%, 3.43% and 3.89% of protein; 16.66%, 19.09% and 11.37% of moisture; 4.57%, 3.68% and 7.28% of total ash and water activity (Aw) of 0.41, 0.44 and 0.44, respectively. Evaluation of antioxidant activities using ferric reducing ability of plasma (FRAP), 1,1-diphenyl-2-pycrylhydrazyl (DPPH) and Trolox/ABTS equivalent antioxidant capacity (TEAC) revealed that the skins fraction exhibits highest antioxidant activities (p<0.05) followed by whole fruit and berries fractions. The antioxidant activities were significantly correlated (p<0.05) with total phenolic and total flavonoid content but not to anthocyanins. Considering the nutritional values it contained, B. angulata is another good source of natural antioxidants with significant health benefits and high value for commercialization.